Molecular markers for the identification of BNI capacity in chromosome addition lines and their use in marker-assisted breeding - Vishwakarma, Manish Kumar; Kumar, Uttam; Bhati, Pradeep Kumar; Dreisigacker, Susanne; Thiyagarajan, Karthikeyan; Kishii, Masahiro; Joshi, Arun Kumar (Springer Nature, 2025)
Wild relatives of wheat possess biological nitrification inhibition (BNI) capacity, which hinders soil nitrification and can be transferred to cultivated bread wheat through methods of wide crossing. The chromosome addition lines (CAL) with Lr#N translocations in chromosome 3BS of wheat were crafted through crosses between Leymus racemosus and Triticum aestivum. Since the CAL has been shown to possess both BNI and other advantageous traits for wheat improvement, it was utilized as a donor to transfer improved BNI capacity into recently released wheat varieties as recipient parents. Marker-assisted backcrossing was deployed. We validated the Sequence Tagged Site markers developed from de-novo sequencing of the Leymus species, along with Kompetitive Allele-specific PCR markers, to identify both translocated and non-translocated lines of wheat and detect the introgressed segments in backcrossed progenies across various cross combinations. For marker validation, Genomic In-situ Hybridization was used to confirm the presence of the translocated region in the recipient lines.